Non‐suicidal self‐injury in US military veterans: Results from the National Health and Resilience in Veterans Study. (24th October 2021) - Kachadourian, Lorig K.; Nichter, Brandon; Herzog, Sarah; Norman, Sonya B.; Sullivan, Tami; Pietrzak, Robert H.
Abstract: Background: To evaluate the prevalence of lifetime non‐suicidal self‐injury (NSSI) among US military veterans and identify sociodemographic, military, psychiatric and clinical correlates associated with NSSI. Methods: Data were analysed from the 2019–2020 National Health and Resilience in Veterans Study, a contemporary, nationally representative survey of 4069 US veterans. Outcomes measured included lifetime history of NSSI, trauma history, lifetime and current DSM‐V mental disorders and lifetime and recent suicidal behaviours. Results: The overall prevalence of lifetime NSSI was 4.2% (95% confidence interval [3.6%, 4.9%]). Multivariable analyses revealed that veterans who endorsed lifetime NSSI were more likely to be younger, female, non‐Caucasian, unmarried or unpartnered, and to have a lower annual household income. Veterans who endorsed lifetime NSSI reported more adverse childhood experiences and lifetime traumas and were more likely to have experienced military sexual trauma. They also were more likely to screen positive for lifetime posttraumatic stress disorder, major depressive disorder (MDD) and substance use disorders and to have attempted suicide. Finally, lifetime NSSI was associated with current MDD, generalized anxiety disorder, and substance use disorders, as well as past‐year suicidal ideation. Conclusion: Results of this study provide the first‐known data on the epidemiology of NSSI in US military veterans. They suggest that certain correlates can help identify veterans who may be at greater risk for engaging in NSSI, as well as the potential prognostic utility of lifetime NSSI in predicting current psychiatric problems and suicide risk in this population.